Illocutionary Acts as Tools of Resistance Against Mainstream Hegemony in Song Lyrics of Nirvana's Come as You Are and You Know You're Right - Muhamad Rifan (CV. Era Digital Nusantara, 2025)
This study examines the illocutionary acts present in the lyrics of Nirvana's Come as You Are and You Know You're Right, focusing on the songwriter's intentions and the communicative functions of each speech act. Using Searle's (1969) theory of illocutionary act types and Leech's (1983) framework of illocutionary functions, the research identifies and classifies 31 non-repeated lyric lines from these songs. A qualitative approach analyzes how each line performs an act such as stating, inviting, expressing, or promising, and how it functions socially and emotionally through collaborative, conflictive, competitive, or convivial purposes. Findings reveal that in Come as You Are, directive acts are most frequent, often used to invite or suggest actions, with collaborative functions aiming for mutual understanding. In contrast, You Know You're Right employs representative and commissive acts not only to describe emotional withdrawal, but as linguistic mechanisms to resist and detach from dominant societal pressures. While collaborative functions foster a shared space for marginalized identities, the prominent conflictive functions elevate Cobain’s internal struggles into a broader critique of social inequality, highlighting the stark friction between the vulnerable minority and the imposing expectations of the mainstream majority. This research concluded that these pragmatic elements, especially the conflictive and withdrawing acts, function as a powerful tool of symbolic resistance. These elements represent the voice of a marginalised subculture minority expressing their alienation and defiance against the expectations of the dominant, mainstream majority.